A combined study of [sup.18]F-FDG PET-CT and fMRI for assessing resting cerebral function in patients with major depressive disorder - Fu, Chang; Zhang, Hongju; Xuan, Ang; Gao, Yongju; Xu, Junling; Shi, Dapeng (Experimental and therapeutic medicine, 2018)
The present study investigated changes in the regional cerebral metabolic rates of glucose uptake (rCMRglc) using [sup.18]F-fluorodeoxyglucose ([sup.18]F-FDG) positron emission tomography (PET) and regional homogeneity (ReHo), together with resting-state blood oxygen level-dependent (BOLD) functional magnetic resonance imaging (fMRI), in patients with major depressive disorder (MDD). In total, 18 patients with untreated MDD and 17 healthy control subjects underwent [sup.18]F-FDG PET and BOLD-fMRI scanning. The MDD patients' cerebral changes, measured as rCMRglc and ReHo values, were mapped and statistically analyzed. Compared with the control group, the patients with MDD had a decreased rCMRglc in the bilateral superior, middle and inferior frontal gyrus, in the bilateral superior and middle temporal gyrus, in the bilateral anterior cingulate cortex, in the bilateral putamen and caudate, and in the left pallidum, but an increased rCMRglc in the bilateral hippocampus and left thalamus. The ReHo values in the patient group were decreased in the bilateral superior and middle frontal gyrus, left pallidum, bilateral putamen and left anterior cingulate cortex, but increased in the right hippocampus and thalamus. No statistically significant differences were identified between decreased metabolism and ReHo brain regions of MDD patients ([chi square] = 9.16; P=0.90) and between increased metabolism and ReHo brain regions ([chi square] = 3.96; P=0.27), when comparing activated brain regions of PET and MRI. The standardized uptake values (SUV) of the bilateral superior, middle and inferior frontal gyrus, bilateral superior and middle temporal gyrus, bilateral putamen, the left caudate and pallidum, the left anterior cingulate cortex, and the bilateral hippocampus and thalamus were correlated with the ReHo (r=0.51-0.83; P<0.05). However, no correlation was detected between the SUV and ReHo in the right caudate and anterior cingulate cortex (r=0.41 and 0.37, respectively; P>0.05). Taken together, these results demonstrated that patients with MDD displayed characteristic patterns regarding changes of brain glucose uptake and ReHo in the resting state. Furthermore, [sup.18]F-FDG PET may be a more sensitive technique compared with BOLD-fMRI for the identification of brain lesions in patients with MDD. Key words: major depressive disorder, regional cerebral metabolic rate of glucose uptake, positron emission tomography, [sup.18]F-fluorodeoxyglucose, functional magnetic resonance imaging, regional homogeneity